The logic of the double social stigmatization of homeless children and teenagers in Capitães da Areia - Ribeiro, Leandro Lima (Estudos Semióticos, 2022)
This study analyzes, in the theoretical and methodological framework  of French discourse semiotics, the contours of a conservative and intolerant  rhetoric that hides, behind its configuration, the violation of human rights of  children and teenagers in street situation in the novel Capitães da Areia (1937),  by Jorge Amado. In this sense, it is shown that, from the point of view of  narrative organization, exclusion as a pragmatic sanction is based on the logic of  double social stigmatization of marginalized subjects: invisibility and  ultravisibility. Furthermore, the novel outlines the actions of the Penal State and  its methodology of punishment and exclusion of the poorest. In summary, a  discontinuity with the project of national identity based on the euphoric  celebration of the mixture and the notion of racial and cordial democracy is  evidenced.